2013
DOI: 10.1371/journal.pone.0074097
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Simulation of Endemic Salmonella enterica Serovar Typhi: The Importance of Long Lasting Immunity and the Carrier State

Abstract: BackgroundTyphoid fever caused by Salmonella enterica serovar Typhi (S. Typhi) remains a serious burden of disease, especially in developing countries of Asia and Africa. It is estimated that it causes 200,000 deaths per year, mainly in children. S. Typhi is an obligate pathogen of humans and although it has a relatively complex life cycle with a long lived carrier state, the absence of non-human hosts suggests that well targeted control methods should have a major impact on disease. Newer control methods incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…For example, we found that the age distribution of typhoid cases in Dhaka, Bangladesh was consistent with a higher basic reproductive number ( R 0 ∼7) in this setting [29]. Furthermore, we estimated the rate of waning immunity to clinical disease ( ε ) to be very low, consistent with another recent modeling study [21]. However, this may be due to the relatively high incidence of typhoid infection in this population leading to continual boosting of immunity through reinfections.…”
Section: Discussionsupporting
confidence: 87%
“…For example, we found that the age distribution of typhoid cases in Dhaka, Bangladesh was consistent with a higher basic reproductive number ( R 0 ∼7) in this setting [29]. Furthermore, we estimated the rate of waning immunity to clinical disease ( ε ) to be very low, consistent with another recent modeling study [21]. However, this may be due to the relatively high incidence of typhoid infection in this population leading to continual boosting of immunity through reinfections.…”
Section: Discussionsupporting
confidence: 87%
“…(2). This is consistent with other studies: an R 0 of 2.8 was estimated in Vellore (India) [24]; a value of 3.4 was found for the reproduction number from an untreated clinical infection in [25]. However in Dhaka, Bangladesh, R 0 for typhoid fever was estimated at 7 [24] (but not all cases of S. typhi cause typhoid fever).…”
Section: R 0 From the Cherry-to-tip Ratio In Reconstructed Treessupporting
confidence: 91%
“…Therefore, determining the prevalence of excreters, including asymptomatic carriers, in any population is important for modeling transmission dynamics and the potential impact of vaccination for this disease [44,45]. The role of S. Typhi carriers in the persistence of typhoid fever in endemic regions has been observed in parts of Chile [46] and Vietnam [47], and the impact of carriers on incident typhoid fever cases is consistent with output from stochastic modeling of typhoid fever transmission [48]. Less information has been documented on the factors that contribute to iNTS transmission.…”
Section: Discussionmentioning
confidence: 75%